The Problem of Magic and Monotheism in the Book of Leviticus - Rüdiger Schmitt (Journal of Hebrew Scriptures, 2008)
The article deals with some of the theses advanced in Mary Douglas’s later works (In the Wilderness, Leviticus as Literature, and Jacob’s Tears), and in particular with her claim that magic and divination were outlawed in the priestly conceptions of the reformed religion of Israel. Her position here relates to her basic thesis that the priestly writings promoted a renewed religion more abstract, more orderly, and more fully theorized than the religions in the Israelite ancient Near Eastern environment. I show that the transformation of Israelite religion in the exilic-post-exilic period was less radical and that the concept of monotheism had no effect on certain ritual practices that could be considered magic, because their concept was in essence theistic.